«Таинственный певец»: к истории русской поэзии 1910-х ‒ начала 1920-х годов - Ustinov, Andrej (Wiener Slawistischer Almanach, 2024)
The essay reconstructs the literary biography of Dmitry (Samuil) Maizel′s, a Petersburg poet who participated in a series of important publishing enterprises of the Silver Age, such as an anthology Eighty Eight Contemporary Poems Selected by Zinaida Gippius (1917) and Arion. Poems (1918). His last major literary appearance was in the almanac 31 Hands (1927), an ultimate collection of poetry that escaped Soviet censorship.